Strategies for mercury speciation with single and multi-element approaches by HPLC-ICP-MS - Favilli, Laura; Giacomino, Agnese; Malandrino, Mery; Inaudi, Paolo; Diana, Aleandro; Abollino, Ornella (Frontiers in Chemistry, 2022)
Mercury (Hg) and its compounds are highly toxic for humans and ecosystems, and their chemical forms determine both their behavior and transportation as well as their potential toxicity for human beings. Determining the various species of an element is therefore more crucial than understanding its overall concentration in samples. For this reason, several studies focus on the development of new analytical techniques for the identification, characterization, and quantification of Hg compounds. Commercially available, hyphenated technology, such as HPLC-ICP-MS, supports the rapid growth of speciation analysis. This review aims to summarize and critically examine different approaches for the quantification of mercury species in different samples using HPLC-ICP-MS. The steps preceding the quantification of the analyte, namely sampling and pretreatment, will also be addressed. The scenarios evaluated comprehend single and multi-element speciation analysis to create a complete guide about mercury content quantification.